0015 Head injury and concussion management in extracurricular sports: a multi-pronged evaluation of the massachusetts 2010 legislation. (26th April 2015) - Brown, Linda; Hackman, Holly; Mills, Julie Kautz; Pavlos, Carlene; Hathaway, Jeanne; Chu, MyDzung; Maguire, Colleen; Lee, Leonard
Abstract : Statement of purpose: In 2013, 20% and 16% of Massachusetts middle and high school athletes, respectively, reported symptoms consistent with a traumatic brain injury (TBI) while playing sports in the past 12 months. The Massachusetts' 2010 legislation aimed to improve the prevention and management of sports related head injuries, thereby promoting brain healing and reducing the risk of serious health consequences among student athletes in grades 6–12. We describe our ongoing evaluation of this law and its associated regulations. Methods/Approach: A multi-pronged evaluation was conducted, consisting of: analyses of mandatory annual school reporting of head injuries; a review of policies from a convenience sample of schools; results from concussion-related questions added to the MA Youth Health Survey (YHS), an anonymous statewide survey of middle and high school students; and, analysis of statewide trends in emergency department (ED) visits for sports related TBI. Results: Compliance with mandated submission of head injury reports by schools increased from 203 schools in 2011/2012 to 554 in 2013/2014. Of the 154 school policies submitted, 4 had all 21 required components. According to the 2013 YHS, 35% of middle and high school athletes who experienced symptoms of a TBI while playing sports stopped playing and got checked by a doctor or nurse; 17% stopped playing but did not get checked; and 48% continued to play. ED rates for sports-associated TBI's which increased in the 12–14 and 15–18 year age groups from 2008 to 2012, decreased from 2012 to 2013. Conclusions: Results indicate that MA schools are making progress in the implementation of state regulations. However, review of school policies and survey findings indicating that nearly half of the student athletes who reported symptoms of a concussion did not stop playing suggests further work is needed to improve student safety. Significance and contribution to the field: Discussion of our multi-pronged evaluation findings and the successes and challenges of the MA law and its associated regulations may benefit other states implementing similar youth sports concussion safety programs and policies.